Sociocultural and domestic influences to online learning in developing countries - Diocleciano Nhatuve; Tsitsi Roselene Bwetenga (Universidade Católica Portuguesa, 2021)
This paper aims to discuss to what extent social, parental and family aspects affect the performance of university students in the Southern Africa Region. Principles of online teaching and learning and the qualitative and quantitative methodologies inform this research. Data comprises information and ideas of students and their parents or guardians, collected through a survey on online teaching and learning processes in the region. Data analyses indicate that over 77% of learners were not satisfied/successful with online learning. Financial challenges, however, are not the main reason of frustration. Only 39% of students report difficulties related to finances. A large number of respondents indicates issues related to negative parental and family involvement, such as lack of parental guidance and encouragement in favour of online learning and denial of this modality of education, as the major problems behind students' frustration, dissatisfaction and failure. It is highlighted, therefore, that positive parental involvement is a key for students' success, especially in the online learning process.